2019
DOI: 10.1089/neu.2018.6143
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Acute Subdural Hematoma in the Elderly: A Fluid-Structure Interaction Study

Abstract: Acute subdural hematoma (ASDH) due to bridging vein (BV) rupture is a frequent and lethal head injury, especially in the elderly. Brain atrophy has been hypothesized to be a primary pathogenesis associated with the increased risk of ASDH in the elderly. Though decades of biomechanical endeavours have been made to elucidate the potential mechanisms, a thorough explanation for this hypothesis appears lacking. Thus, a recently improved finite element head model, in which the brain-skull interface was modelled usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…In recent decades, FE head models have been increasingly used to fill the knowledge gap between external loading, localized brain response, and resultant injury. [24][25][26][27][28][29] Partially inspired by the aforementioned mechanism that axonal elongation triggers TAI occurrence, various endeavors have been made recently to simulate deformation along WM fiber tracts (i.e., the tract-oriented strain). [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Of note, the tract-oriented strain is synonymous with axonal strain or fiber strain, which are both terms used in multiple studies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, FE head models have been increasingly used to fill the knowledge gap between external loading, localized brain response, and resultant injury. [24][25][26][27][28][29] Partially inspired by the aforementioned mechanism that axonal elongation triggers TAI occurrence, various endeavors have been made recently to simulate deformation along WM fiber tracts (i.e., the tract-oriented strain). [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Of note, the tract-oriented strain is synonymous with axonal strain or fiber strain, which are both terms used in multiple studies.…”
Section: Introductionmentioning
confidence: 99%
“…In preference to the Lagrangian-based CSF representation, recent models have employed an arbitrary Lagrangian-Eulerian (ALE) multi-material formulation to describe the subarachnoid CSF combined with a fluid-structure coupling algorithm for the brain-skull interface. [36][37][38][39] However, such a modeling strategy has not been implemented for the brain-ventricle interface to date, especially in traumatic scenarios. This may be partially attributed to a highresolution description of the interfacial geometry being indispensable for fluid-structure interaction (FSI) implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The fluid-like CSF utilizes an elastic solid material with fluid-like constitutive behavior and an equation of state constitutive model [13]. In recent years, many groups have shifted to the use of fluid-structure interaction (FSI) models [14][15][16][17][18]. Since the start of this project, recent work has shown that others are also attempting to use similar numerical methods to simulate FSI of CSF with brain, but with geometrically simplified 2D models [19].…”
Section: Introductionmentioning
confidence: 99%
“…While the importance of including CSF in the numerical simulations is now well-documented [21], the current finite element studies reported in the literature often lack more detailed anatomical structures [12,14,15,[22][23][24][25]. The brain is more complex in structure than what has been described in prior models.…”
Section: Introductionmentioning
confidence: 99%